1, 2, 3 to the zoo - Carle, Eric. (New York : Philomel Books, 1982)
Each car on the train has one more zoo animal than the one before, from the first car with an elephant to the last with ten birds.
Elem. School Library Collection.
School Library Journal.
School Library Media Quarterly (A.A.A.L.).
1.1.
1.1
K-3
Keywords: Counting -- Juvenile literature; Counting; Zoo animals; Counting; Zoo animals